The Woman Problem In The Philosophy Of Malek Bennabi - Bellour, Leila (جامعة الوادي university of eloued, 2023)
The woman problem is a longstanding, complex, and central issue in the history of philosophy. This paper discusses Malek Bennabi’s views regarding the role of women and his recommendations for the treatment of such heated debatable issues as feminism and the role of women in social reforms and civilizational advancement. As this paper evinces, Bennabi’s conceptions of the woman’s role is in tandem with the teachings of Islam
مقال
Keywords: woman ; feminism ; woman dress ; civilization ; Malek Bennabi